Training online faculty: a phenomenology study - Kang, Haijun (My University, 2011)
Literature on training faculty to teach online still dwells on the issues explored a decade ago. To make a substantial move in this area, it is necessary to re-evaluate the essence of training in the context of producing qualified online faculty to teach quality online courses. Employing a phenomenological approach, this study examines seven online faculty’s lived training experiences and observed that there existed incidental factors that could affect the quality of training. Further data analysis indicated that it was the different levels of understandings of “training” between different parties that led to variations in the quality of training. “There is a whole [training] world that’s going on out there … I’m just not interested… because that’s not my world,” said one research participant. Therefore, different parties involved in training online faculty should look at training from a systems approach and view training as an opportunity (1) to transfer knowledge and skills necessary for conducting quality online instruction; (2) to remove barriers preventing faculty from teaching online; and (3) to transform traditional faculty members into highly qualified online faculty.
Keywords: Online faculty; Training quality; Phenomenology study